Serial measurements of high-sensitivity cardiac troponin T after exercise stress test in stable coronary artery disease. (June 2013) - Axelsson, Anna; Ruwald, Martin Huth; Dalsgaard, Morten; Rossing, Kasper; Steffensen, Rolf; Iversen, Kasper
Abstract Objective: The aim was to assess serial measurements of high-sensitivity cardiac troponin T (hs-cTNT) post-exercise in patients with stable coronary artery disease (CAD). Methods: Twelve patients with positive coronary angiograms (CAD positives) and 12 controls performed an exercise stress test. Results: CAD positive had higher baseline and peak concentrations of hs-cTNT than controls. Significant increases in hs-cTNT were seen in both groups after exercise. In two-third of patients the peak in hs-cTNT was above the 99th percentile. Conclusion: hs-cTNT is higher in patients with stable coronary disease than in controls and exceeds the diagnostic cut-off value for myocardial infarction in a majority of patients with CAD after exercise.